Application and interpretation of core elements of the 2015 NMOSD diagnostic criteria in routine clinical practice - Carnero Contentti, Edgar; Rojas, Juan I.; Alonso, Ricardo; Yeaman, Michael R.; Weinshenker, Brian G. (Frontiers in Immunology, 2024)
BackgroundWe evaluated comprehension and application of the 2015 neuromyelitis optica spectrum disorder (NMOSD) criteria core elements by neurologists in Latin America (LATAM) who routinely diagnose and care for NMOSD patients by (i) identifying typical/suggestive NMOSD syndromes, (ii) detecting typical MRI NMOSD lesions and meeting MRI dissemination in space (DIS) criteria, and (iii) evaluating historical symptoms suggestive of NMOSD.MethodsWe conducted an anonymous, voluntary, self-administered web- and case-based survey cross-sectional study from October 2023 to January 2024 of neurologists identified through the LACTRIMS database. Questions were presented first through iterative clinical cases or imaging, followed by questions directly evaluating comprehension of definitions. “Correct” responses were based on the 2015 criteria and adjudicated by the consensus of the experts leading the project.ResultsA total of 106 neurologists (60.3% female; mean age: 46.6 ± 12.5 years) were included. Between 10.4% and 49.1% of neurologists inaccurately identified clinical or paraclinical aspects for DIS and 32.1% accurately identified the three non-cardinal (brainstem, diencephalic, and cerebral) syndromes for seronegative patients. Between 35.8% and 64.1% of neurologists identified the “optimal timing” of AQP4-IgG testing (e.g., during an attack or before receiving immunosuppressant treatments, among others); 56.6% considered live cell-based assay as the gold standard method for serological testing. Most neurologists accurately identified typical NMOSD MRI lesions, but periventricular, juxtacortical/cortical, fluffy infratentorial, corticospinal tract, and hypothalamic lesions were frequently misidentified.ConclusionClinical scenarios were identified where the 2015 NMOSD criteria were susceptible to misinterpretation and misapplication by expert neurologists in LATAM. Implementing collaborative educational initiatives could improve NMOSD diagnosis and raise patient care standards.